Modelling human upper-airway dynamics and dysfunction - Tetlow, George A. (Curtin University, 2012)
Repetitive closure of the upper-airway characterises obstructive sleep apnea. It disrupts sleep causing excessive daytime drowsiness, and is linked to hypertension and cardiovascular disease.Previous studies simulating the underlying fluid mechanics of two-dimensional channel flow are based upon velocity-driven boundaries with symmetric positioning of the soft-palate. In the first part of the present work the two-dimensional work of Balint (2001) is extended to a pressure-driven model where the stability solutions space mapped for the soft-palate, symmetrically placed within viscous channel flow. As a result of this work the modelling of Obstructive Sleep Apnoea (OSA) it is proposed that modelling should focus on nasal breathing as the first indicator for the presence of OSA. Numerical simulations reveal the appearance of amplification of soft-palate displacement over several breathing cycles with asymmetric positioning of the soft-plate and for nasal breathing (single channel flow). Such events increase airway hydraulic resistance at the start of inhalation, a vulnerably period of the breathing cycle for collapse of the pharynx.In the second part of the present work three-dimensional studies are conducted for duct flow and flow through an anatomically correct reconstructed geometry, supporting the findings of the two-dimensional work of the first part. Moreover, extending understanding of anatomical interactions, through development of a three-dimensional geometry reconstruction based on an airway at the end of inhalation. Here the geometry is reconstructed from quantitative date linked to the breathing cycle, captured via an in vivo method using an adapted endoscope technique. Simulations reveal flow mechanisms that produce low-pressure regions on the side walls of the pharynx and on the soft-palate within the pharyngeal section of minimum area. Soft-palate displacement and lateral pharynx-wall deformations reduce further the pressures in these regions creating forces that would tend to narrow the airway owing to flow curvature. These phenomena suggest a mechanism for airway closure in the lateral direction as observed in an bronchoscope study conducted as part of this thesis.